N‐([1, 1ʹ‐biaryl]‐4‐yl)‐1‐naphthamide‐based scaffolds synthesis, their cheminformatics analyses, and screening as bacterial biofilm inhibitor. (1st November 2021) - Ejaz, Saba; Zubair, Muhammad; Rasool, Nasir; Ahmed, Faiz; Bilal, Muhammad; Ahmad, Gulraiz; Altaf, Ataf A.; Shah, Syed A. A.; Rizwan, Komal
Abstract: Naphthamides have pharmacological potential as they express strong activities against microorganisms. The commercially available naphthoyl chloride and 4‐bromoaniline were condensed in dry dichloromethane (DCM) in the presence of Et3 N to form N ‐(4‐bromophenyl)‐1‐naphthamide (86%) (3 ). Using a Pd(0) catalyzed Suzuki–Miyaura Cross‐Coupling reaction of (3 ) and various boronic acids, a series of N ‐([1, 1ʹ‐biaryl]‐4‐yl)‐1‐naphthamide derivatives (4a–h ) were synthesized in moderate to good yields. The synthesized derivatives were evaluated for cytotoxicity haemolytic assay and biofilm inhibition activity through in silico and in vitro studies. Molecular docking, ADME (absorption, distribution, metabolism, and excretion), toxicity risk, and other cheminformatics predict synthesized molecules as biologically active moieties, further validated through in vitro studies in which compounds (4c ) and (4f ) showed significant haemolytic activity whereas (4e ) exhibited an efficient biofilm inhibition activity against Gram‐negative bacteria Escherichia coli and Gram‐positive bacteria Bacillus subtilis . When forming biofilms, bacteria become resistant to various antimicrobial treatments. Currently, research is focused on the development of agents that inhibit biofilm formation, thus the present work is valuable for preventing future drug resistance.